Bos Salad Competitive Advantages Analysis Using Strategic Position and Action Evaluation (SPACE) Matrix Analysis - Viky Octaviyona (Politeknik Negeri Bengkalis, 2023)
This study aims to determine the right strategy to be applied to the Bos Salad Business by using a Strategic Position and Action Evaluation. In this sample, there are three business ventures, namely, bos salad as an internal party as the party being studied, Floor Cafe and New Fanelco as external parties who are the closest competitors to Bos Salad. Data collection methods in this study using questionnaires and interviews. The variables used in this study are four variables. The analytical method uses a parabolic non-liner secular trend using OLS (Ordinal Least Square). Based on the results of the research conducted, the right strategy for Bos Salad is an Aggressive Strategy, in which Financial Strength and Competitive Advantage dominate the business.